System and method for data file upload over a communication network - Syed Mohamed, Syed Abd. Rahman Al-Hadad; Tan, Chen Hong; Ramli, Abdul Rahman (2009)

(untitled)
The present invention provides the solution of using facsimile device as the uploading tool to upload database into internet remotely and automatically. This invention utilizes the remote and scanning function of facsimile to carry out the database-uploading job automatically. This invention focuses on duplicating the original document on the client side and displaying its contents directly in the Internet. This should provide efficiency and convenience for anyone who wants to upload fax contents into the Internet without mastering the aspect of technical knowledge. This invention integrates two popular devices: personal computer and facsimile and utilizes telephone line as the transmission medium.